Abdominal imaging can misdiagnose submassive hepatic necrosis as cirrhosis in acute liver failure. (6th May 2013) - Kim, Andrew I.; Han, Steven‐Huy; Tran, Doan‐Trang; Sullivan, Peggy; Lassman, Charles; Raman, Steve; Zimmerman, Peter; Chin, Eva E.
Abstract Patients with acute liver failure (ALF) can be listed status I for liver transplantation (LT) whereas patients with cirrhosis must follow the MELD scoring system. Liver imaging can mistakenly diagnose submassive hepatic necrosis in ALF as cirrhosis. The purpose of our study was to assess the accuracy of ultrasound (US) and computed tomography (CT) in distinguishing cirrhosis from ALF. All patients listed for ALF and transplanted during the study period were included. Controls were age‐ and gender‐matched cirrhotic patients who underwent LT during the same period. Abdominal US or CT scans obtained on all patients were independently reviewed by three blinded abdominal radiologists. Explants from all patients were reviewed by two blinded pathologists, and histological diagnosis was correlated with radiological diagnosis. Forty‐one patients with ALF and 42 patients with cirrhosis were analyzed. Univariate and multivariate analyses both revealed overall accuracy of 85% for ultrasound and 93% for CT. US and CT scans both provide high levels of accuracy in terms of discriminating ALF from cirrhosis but measures taken to determine whether a patient has ALF vs. cirrhosis needs to approach 100% accuracy. Thus, imaging studies alone should not definitively diagnosis one etiology of liver failure over the other.